FAKTOR YANG MEMPENGARUHI GREEN PRODUCT PURCHASE DECISIONS PADA PRODUK PERBEKALAN KESEHATAN RUMAH TANGGA RAMAH LINGKUNGAN DI SURABAYA - Fatimah Khoirun Nisa’ (Perpustakaan Universitas Surabaya, 2019)
Abstrak - Penelitian ini bertujuan untuk mengetahui dan membuktikan pengaruh supporting environmental protection, drive for environmental responsibility, green product experience, environmental friendliness of companies, dan social appeal terhadap green product purchase decisions pada produk PKRT ramah lingkungan di Surabaya. Pengolahan data penelitian ini menggunakan Structural Equation Modelling (SEM) dengan program Statistical Package for Social Sciences (SPSS) versi 18 dan LISREL versi 8.7. Obyek penelitian ini adalah orang yang membeli dan menggunakan produk PKRT ramah lingkungan minimal tiga bulan terakhir. Jumlah sampel dalam penelitian ini berjumlah 185 responden yang diambil dengan pendekatan purposive sampling. Hasil penelitian ini menunjukkan bahwa supporting environmental protection berpengaruh positif dan signifikan terhadap green product purchase decisions, drive for environmental responsibility tidak memiliki pengaruh terhadap green product purchase decisions, green product experience berpengaruh positif dan signifikan terhadap green product purchase decisions, environmental friendliness of companies berpengaruh positif dan signifikan terhadap green product purchase decisions, dan social appeal tidak memiliki pengaruh terhadap green product purchase decisions. Kata kunci: supporting environmental protection, green product experience, green product purchase decisions Abstract - This research aims to know and prove the existence of supporting environmental protection, drive for environmental responsibility, green product experience, environmental friendliness of companies, and social appeal to green product purchase decisions on environmentally friendly PKRT products in Surabaya.This research data processing using Structural Equation Modeling (SEM) with Statistical Package for Social Sciences (SPSS) version 18 and LISREL version 8.7. The object of this research is people who buy and use environmentally friendly products PKRT at least the last three months. The number of samples in this study amounted to 185 respondents taken with the approach of purposive sampling.The results of this study indicate that supporting environmental protection has a positive and significant effect on green product purchase decisions, the drive for environmental responsibility has no effect on green product purchase decisions, green product experience has a positive and significant effect on green product purchase decisions, environmental friendliness of companies positively and significant to green product purchase decisions, and social appeal has no effect on green product purchase decisions. Keywords: supporting environmental protection, green product experience, green product purchase decisions